Targeting East Coast fever control strategies based on the assessment of biological risk - Kiara, Henry K.; O'Callaghan, C.J.; Randolph, Thomas F.; McDermott, John J.; Perry, Brian D. (International Society for Veterinary Epidemiology and Economics, 2000)
This paper studies East Coast fever (Theileria parva infection) risk in four district smallholder-farming areas of Kenya representing a range of epidemiological states of the disease. The areas include Kakamega, where indigenous cattle are intensively grazed with minimal tick control under moderate to high tick challenge; Uasin Gishu, where only primarely exotic cattle are extensively grazed under moderate challenge; Makuyu, where a mix of indigenous and cross-bred cattle are intensively grazed under moderate challenges; and Kiambu, where exotic cattle are kept almost exclusively under zero grazing with low challenge.